Implementasi Load Balancing menggunakan Algoritme Least Connection dengan Agen Psutils pada Web Server - Muhammad Sholeh; Widhi Yahya; Primantara Hari Trisnawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Social media and news sites are services on the Internet that are most visited by Internet users. These services are required to be able to handle very high traffic.. If the service uses a single web server, it can cause a Single Point of Failure. The solution for that problem is to use a method of load balancing. Load balancing is a method that can distribute traffic to multiple servers based on the algorithm used. This research develop the Least Connection algorithm for load balancing in the Software Defined Network (SDN). Least Connection is a load balancing algorithm that will direct traffic to web servers that have the least connection. This research uses an agent called Agent Psutils. This agent send information to SDN Controller about the number of active connections of web servers. From this information, SDN Controller can direct traffic to web servers that have the least connection. The results of the study show that the Least Connection algorithm with Agent Psutils can distribute traffic based on the number of active connections on server. Then, when comparing the Least Connection algorithm based on Agent Psutils (LC Agent Psutils) with Least Connection based on Expired Flow (LC Flow). LC Agent Psutils can send data measuring 1.2 GigaBytes while LC Flow cannot complete the data transmission process. At 400 requests, LC Agent Psutils have a smaller response time than Round Robin and LC Flow. Where the response time of the LC Agent Psutils is 242.51 ms, while the Round Robin and LC Flow are 261.61 ms and 279.81 ms.